International Myeloma Working Group guidelines for the management of multiple myeloma patients ineligible for standard high-dose chemotherapy with autologous stem cell transplantation - Palumbo, A.; Sezer, O.; Kyle, R.; Miguel, J.S.; Orlowski, R.Z.; Moreau, P.; Niesvizky, R.; Morgan, G.; Comenzo, R.; Sonneveld, P.; Kumar, S.; Hajek, R.; et al. (Leukemia, 2009)
In 2005, the first guidelines were published on the management of patients with multiple myeloma (MM). An expert panel reviewed the currently available literature as the basis for a set of revised and updated consensus guidelines for the diagnosis and management of patients with MM who are not eligible for autologous stem cell transplantation. Here we present recommendations on the diagnosis, treatment of newly diagnosed non-transplant-eligible patients and the management of complications occurring during induction therapy among these patients. These guidelines will aid the physician in daily clinical practice and will ensure optimal care for patients with MM.